2017
DOI: 10.4149/bll_2017_030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of platelet indices as a useful marker in papillary thyroid carcinoma

Abstract: OBJECTIVES: Our aim was to investigate platelets (PLT) and their indices-mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT)-in the differential diagnosis of benign and malignant thyroid disorders. BACKGROUND: Platelet and platelet indices recently started to be defi ned as an useful clinical marker in cancer patients. Their higher reproducibility rates and low cost provide them a wide range of usage. MATERIAL AND METHODS: One-hundred and sixty patients were divided into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 17 publications
2
37
1
1
Order By: Relevance
“…It decreased to 7.60 fL (p = 0.005), so the postoperative MPV levels of patients and healthy controls were comparable. The same association was confirmed by other studies, which showed that MPV was significantly higher in the group of patients with thyroid cancer than in the benign group [25,26]. However, the prognostic role of MPV in this type of cancer has not yet been established.…”
Section: Evaluation Of Various Hematological Indices In Patients Withsupporting
confidence: 78%
“…It decreased to 7.60 fL (p = 0.005), so the postoperative MPV levels of patients and healthy controls were comparable. The same association was confirmed by other studies, which showed that MPV was significantly higher in the group of patients with thyroid cancer than in the benign group [25,26]. However, the prognostic role of MPV in this type of cancer has not yet been established.…”
Section: Evaluation Of Various Hematological Indices In Patients Withsupporting
confidence: 78%
“…PCT, a factor that is calculated by PC and MPV, is now generally recognized to reflect platelet activity and the percentage of platelets in blood 19 . To date, PCT is only found to be higher in epithelial ovarian cancer, papillary thyroid carcinoma 14 , and pancreatic adenocarcinoma 46 . Our results firstly showed that PCT was increased in CRC patients.…”
Section: Discussionmentioning
confidence: 98%
“…New automated hematologic analyzers enabled to measure platelet count (PC) and platelets parameters with low cost. Parameters that are related to platelet are known as platelet indices, which mainly include platelet count (PC), mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT) 14 17 . MPV shows the average platelet volume in the blood, while PDW reflects the heterogeneity in platelet volume 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The plateletcrit is determined by the formula platelet count times MPV divided by 10 4 , and the normal range for plateletcrit is 0.22−0.24% [23]. In a study of patients with papillary thyroid carcinoma (PTC), the plateletcrit ranges were 0.24±0.05 in the group with PTC and 0.17±0.02 in the control group, with a significant difference between the two groups (P < 0.01) [24]. In the present study, the plateletcrit range was 0.0870-0.3802% and the cut-off value was 0.2755% according to maximally selected rank statistics using R (maxstat package) software.…”
Section: Discussionmentioning
confidence: 99%